Genomic Regions, Molecular Markers, and Flanking Genes of Metribuzin Tolerance in Wheat (Triticum aestivum L.) - Kurya, Benjamin; Mia, Md Sultan; Liu, Hui; Yan, Guijun (Frontiers in Plant Science, 2022)
Understanding the genetics of metribuzin (a group C herbicide) tolerance in wheat is vital in developing tolerant cultivars to improve wheat productivity in dryland farming systems. This study investigated metribuzin tolerance in wheat by conducting a Genome-wide Association Studies (GWAS) with a panel of 150 wheat genotypes of diverse genetic backgrounds and genotyped them with the wheat 90K SNP genotyping assay. The phenotyping was conducted in a temperature-controlled glasshouse at The University of Western Australia (UWA). Genotypes were sprayed with a metribuzin dose of 400 grams active ingredient (g. a.i.) ha-1 as pre-emergent in a specialised spraying cabinet and transferred to the glasshouse where tolerance level of the genotypes was assessed by measuring the relative reduction in chlorophyll content of the leaves. The decrease in chlorophyll content of the treated plants compared to the control was regarded as the phytotoxic effects of metribuzin. GWAS analysis following a mixed linear model revealed 19 genomic regions with significant marker-trait associations (MTAs), including ten on chromosome 6A, three on chromosome 2B and one on chromosomes 3A, 5B, 6B 6D, 7A and 7B, respectively. Sequences of the significant markers were blasted against the wheat genome, IWGSC RefSeq V1.0, and candidate genes having annotations related to herbicide tolerance in wheat, especially in pathways reported to be involved in metribuzin tolerance, such as cytochrome P450 pathways and ATP Binding Cassette (ABC) superfamilies, were identified in these genomic regions. These included TraesCS6A01G028800, TraesCS6A02G353700, TraesCS6A01G326200, TraesCS7A02G331000, and TraesCS2B01G465200. These genomic regions were validated on 30 top tolerant and 30 most susceptible genotypes using five closest SSR makers to the flanked SNPs. Sufficient polymorphism was detected on two makers (wms193 and barc1036) that were found to differentiate between the susceptible and tolerant alleles and a t-test analysis of the phenotypic data shows a significant (p-value < 0.001) difference suggesting that these markers can be used for marker-assisted selection (MAS) in metribuzin studies and wheat breeding programs.